Índice de sustentabilidade municipal: uma abordagem fuzzy para um sistema de apoio a decisão - Soares, Luiz Fernando da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Change the behavior and habits of people, promoting sustainable production and consumption, has been cause for investments and actions by Governments to promote sustainability as a development model. Although many jobs have been developed over the past years in the creation of indices and measurement of sustainability, few are complete in order to take into account the economic, environmental and social aspects subtext in the concept of sustainable development. Thus, this dissertation presents the development of an index to evaluate the degree of sustainability of municipalities from indicators of the social dimensions, demographic, economic and environmental. The methodology of compiling the index was based on the concepts of Fuzzy set theory that contributed to the design of a system based on a specific knowledge and synthesizing several complex information of direct and easy to understand way. The index has been applied to all 5,565 municipalities in Brazil generating a national sustainability and scenario enabling as an effective instrument in aid to decision-making of managers that can from the results revealed indicate needs and priorities for the formulation, monitoring and evaluation of public policies.

Mudar o comportamento e os hábitos das pessoas, privilegiando uma produção e um consumo sustentável, tem sido motivo de investimentos e de ações por parte dos governos para promover a sustentabilidade como modelo de desenvolvimento. Embora muitos trabalhos tenham sido desenvolvidos ao longo dos últimos anos na criação de índices e mensuração da sustentabilidade, poucos são completos no sentido de levar em conta os aspectos econômicos, ambientais e sociais subentendidos no conceito de desenvolvimento sustentável. Dessa forma, esta dissertação apresenta o desenvolvimento de um índice para avaliar o grau de sustentabilidade dos municípios a partir de indicadores das dimensões sociais, demográficas, econômicas e ambientais. A metodologia de elaboração do índice fundamentou-se nos conceitos da Teoria dos Conjuntos Fuzzy o que contribuiu para a concepção de um sistema baseado em um conhecimento específico e que sintetiza várias informações complexas de maneira direta e de fácil compreensão. O índice foi aplicado a todos os 5.565 municípios brasileiros gerando um cenário de sustentabilidade nacional e habilitando-se como um instrumento efetivo no auxílio à tomada de decisão dos gestores que podem a partir dos resultados revelados indicar necessidades e prioridades para a formulação, monitoramento e avaliação de políticas públicas.
Municipal sustainability index: an approach to fuzzy for a decision support
Keywords: Sustentabilidade; Indicadores ambientais; Lógica difusa